1989
DOI: 10.1103/physrevlett.62.59
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-Resolution Imaging of Close-Packed Metal Surfaces by Scanning Tunneling Microscopy

Abstract: The resolution of individual atoms in scanning-tunneling-microscopy (STM) images of Al(lll) is demonstrated. From results of gap-width and energy-dependent measurements the corrugation observed in the STM images cannot reflect the electronic structure of the Al surface near £>, as usually assumed for such images, but must be due to tip-surface interactions. On the basis of an investigation of the process of tip preparation, an elastic deformation of the frontmost end of the tip mediated by adhesive tipsurface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
65
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 290 publications
(70 citation statements)
references
References 10 publications
4
65
1
Order By: Relevance
“…[1][2][3][4][5][6][7] In the meantime, the origin of atomic resolution in each particular case still cannot be easily deduced in a straightforward manner despite substantial experimental and theoretical efforts. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] In the early years of STM, the concept of atomic resolution on metals was understood in terms of a single tip orbital of s-like character being responsible for the surface images. 8,9 However, this concept was unable to explain tip electronic structure effects reported in the literature for the first time by Tromp et al 10 as well as giant atomic corrugations frequently observed in real experiments on various metal surfaces including close-packed surfaces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7] In the meantime, the origin of atomic resolution in each particular case still cannot be easily deduced in a straightforward manner despite substantial experimental and theoretical efforts. [8][9][10][11][12][13][14][15][16][17][18][19][20][21] In the early years of STM, the concept of atomic resolution on metals was understood in terms of a single tip orbital of s-like character being responsible for the surface images. 8,9 However, this concept was unable to explain tip electronic structure effects reported in the literature for the first time by Tromp et al 10 as well as giant atomic corrugations frequently observed in real experiments on various metal surfaces including close-packed surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 However, this concept was unable to explain tip electronic structure effects reported in the literature for the first time by Tromp et al 10 as well as giant atomic corrugations frequently observed in real experiments on various metal surfaces including close-packed surfaces. Elastic deformation of the tip apex [11][12][13][14][15] and electronic structure effects [17][18][19][20][21] were mainly considered in the literature as two possible mechanisms of corrugation enhancement in STM experiments. One of the explanations of the experimentally observed atomic features with large corrugation heights was given by Chen [18][19][20] in terms of the actual electronic states on realistic tips.…”
Section: Introductionmentioning
confidence: 99%
“…This distance range covers more than seven orders of magnitude in the tunneling current. In addition, the method breaks down completely on close packed metal surfaces, where measured corrugations exceed the values obtained from constant density contours by up to one order of magnitude [8][9][10].…”
mentioning
confidence: 99%
“…The tip in the high corrugation experiments was therefore atomically sharp and covered by comparatively few Al atoms. The experimental corrugation amplitudes reported in [10] have remained a puzzle for more than 15 years. Here, we find the solution of this puzzle: as for Al the surface atoms are less strongly bound to the surface than for noble metals, their outward relaxation under tunneling conditions is very large.…”
mentioning
confidence: 99%
See 1 more Smart Citation